The Use of Evidence Within Policy Evaluation in Health in Ghana: Implications for Accountability and Democratic Governance. (September 2015) - Vecchione, Elisa; Parkhurst, Justin
Abstract : The use of evidence in policymaking is commonly considered a good practice of democratic governance by improving accountability, effectiveness, and stakeholders' involvement in policy decisions. The features of this practice, however, remain vague in the general discourse of evidence‐based policymaking (EBPM) with the risk of obscuring important governance and legitimacy implications. In policy evaluation especially, the use of evidence can be critical to translate technical measurements of policy achievements into political values for shaping future policy directions. We present a case study based on the health policy review process in Ghana in order to discuss how institutionalized evidentiary practices used in policy evaluation affect structures and processes of democratic governance. Drawing on qualitative interviews with international and local actors, we reflect on how the evidence review process—a process agreed in collaboration with development partners—links to the evidence advisory system and the accountability systems in place. We find that the uses of evidence promoted by international donors within the evaluation process actually creates disconnect with the national accountability system in place, with implications for democratic governance.